A Study on Medicinal Plants and uses as Anti- Microbial Agent: Exploring the Therapeutic Potential of Medicinal Plants (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Medicinal plants have played an important role in the evolution of traditional Indian medicinein India. There are an estimated 70,000 plant species that have been utilised for medical purposes atsome point or another. Conventional medications may be isolated or synthesised using herbs as astarting point. The Chinese pharmacopoeia contains about 5,700 traditional remedies, the majority ofwhich are derived from plants, while over 2000 Ayurvedic practitioners felt that plant species hadtherapeutic worth. Although complete plants are seldom employed, around 500 herbs are still used intraditional medicine.